Two new species of Balacha (Insecta: Hemiptera: Cicadellidae: Cicadellinae) from Brazil with comments on their phylogenetic position and biogeography - Quintas, Victor; Takiya, Daniela M.; Cavichioli, Rodney R.; Mejdalani, Gabriel (Zootaxa, 2020)
The sharpshooter genus Balacha Melichar, 1926 has seven recognized species and is distributed in southern South America (Argentina, Brazil, Paraguay, and Uruguay). Here, two new Brazilian species of this genus are described and illustrated, one (B. ancora sp. nov.) from Serra do Caraça and Serra do Cipó (Minas Gerais State) and another (B. nigroflava sp. nov.) from Ponta Grossa (Paraná State) and Passo Fundo (Rio Grande do Sul State). Based on 67 morphological characters, we carried out a parsimony analysis to estimate the phylogenetic position of the two new species. Using implied weighting in TNT, a single topology within Balacha was obtained with k values that varied from 1.599 to 7.412. In this topology, the two new taxa appeared within the clade of black Balacha species. A biogeographical analysis (S-DIVA) suggested that the ancestral area of distribution of Balacha was the Atlantic Forest domain. Balacha species were so far known to have only Eryngium (Apiaceae) species as host plants. Here we report a new host plant for the genus: B. ancora sp. nov. specimens were collected on Actinocephalus polyanthus (Eriocaulaceae). Balacha similis and B. rubripennis are newly recorded from Argentina and specimens of the latter have a very distinct color pattern from the typical Brazilian specimens. Finally, a key to species and maps showing the known distribution of the genus are given (several state records of species are also provided).